USE OF PENICILLIN V IN CHILDREN WITH SICKLE CELL DISEASE - Lopes Carneiro, Lara Rafaelly; Menezes Azevedo, Maria de Fátima; Matos Albuquerque, Maria Zenaide (Cadernos ESP, 2024)
To evaluate the use of the drug penicillin V (Phenoxymethylpenicillin) by pediatric patients with sickle cell disease in an outpatient clinic of a Children’s hospital in Fortaleza, through the identification of Medication-Related Problems (DRP) and analysis of the socioeconomic profile. The study took place between March and April 2021, and was carried out using a questionnaire on the use of Pencillin V dispensed in the unit, as a form of storage and dosage. Afterwards, pharmaceutical guidance was provided and an informative folder about the medicine was delivered. 45 caregivers of children with sickle cell disease using penicillin V were interviewed, 86.7% (40) female and 13.3% (5) male. 59 non-conformities were identified regarding the use of the medication. Therefore, it is important to emphasize the importance of adequate dispensing, in order to guarantee the effectiveness and safety of the treatment.